2016
DOI: 10.1176/appi.ps.201600089
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Treatment in a Day Hospital for Adolescents: A Case of Good Practice

Abstract: The dynamics of adolescence require adjustments in psychiatric treatment because of the challenges of this developmental stage in life. This column describes the Day Hospital for Adolescents (DHA) of the Institute of Mental Health in Belgrade, Serbia, which was established in December 2007. The DHA is a holistic program for the treatment of youths ages 15-25 with emotional disorders. The multicomponent therapeutic program includes individual treatment, several group therapeutic activities, and work with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Review of the empirical literature evaluating non‐DBT‐A PHPs indicated a proclivity among PHP program directors to use the systemic nature of a milieu to accomplish psychodynamic therapy goals, which are reinforced through social learning (Bradic et al, ; Goldstein et al, ; Kennair, Mellor, & Brann, ; Lenz, Del Conte, Lancaster, Bailey, & Vanderpool, ; Preddy, Musella, Parade, Walters, & Hunt, ). Some of these approaches to treating clients’ mental health symptoms have a singular pronounced therapeutic identity, such as cognitive behavior therapy (Bradic et al, ; McHugh et al, ), and the predominant trend among published studies was to implement an eclectic approach featuring many types of interventions across several modalities. Generally speaking, these approaches are eclectic in nature and feature many intervention types across several modalities of treatment.…”
Section: Empirical Status Of Dbt‐amentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the empirical literature evaluating non‐DBT‐A PHPs indicated a proclivity among PHP program directors to use the systemic nature of a milieu to accomplish psychodynamic therapy goals, which are reinforced through social learning (Bradic et al, ; Goldstein et al, ; Kennair, Mellor, & Brann, ; Lenz, Del Conte, Lancaster, Bailey, & Vanderpool, ; Preddy, Musella, Parade, Walters, & Hunt, ). Some of these approaches to treating clients’ mental health symptoms have a singular pronounced therapeutic identity, such as cognitive behavior therapy (Bradic et al, ; McHugh et al, ), and the predominant trend among published studies was to implement an eclectic approach featuring many types of interventions across several modalities. Generally speaking, these approaches are eclectic in nature and feature many intervention types across several modalities of treatment.…”
Section: Empirical Status Of Dbt‐amentioning
confidence: 99%
“…Generally speaking, these approaches are eclectic in nature and feature many intervention types across several modalities of treatment. For example, some authors have reported a statistically significant treatment effect for programs featuring use of assertiveness training, art and music therapy, social skills development, behavioral planning, and psychodrama workshops (Bradic et al, ; Kennair et al, ; Lenz et al, ). These interventions have been delivered within multiple modalities, including individual, group, and family‐based interventions, to promote the development and generalization of skill use within the context of a systems‐informed milieu (Goldstein et al, ; Preddy et al, ).…”
Section: Empirical Status Of Dbt‐amentioning
confidence: 99%
“…Dominiranje simptoma depresivnosti i anksioznosti kod adolescenata koji se leče u uslovima parcijalne psihijatrijske dnevne hospitalizacije je višestruko dokumentovan podatak [19]. Iako su depresija i anksioznost označeni kao zasebni dijagnostički entiteti, postoji značajno preklapanje između ove dve kategorije kako u pogledu fenomenologije, komorbiditeta bioloških markera tako i u pogledu tretmana [20].…”
Section: Diskusijaunclassified